PROGRAM KKN IAKN PALANGKA RAYA DI DESA GARUNG: PEMBUATAN BAK SAMPAH, EDUKASI KEBERSIHAN, AKSI BERSIH, DAN PEMBENTUKAN SATGAS RELAWAN SEBAGAI UPAYA PENGUATAN KEBERSIHAN LINGKUNGAN - Pransinartha; Isa Andreyanku Lana; Willy D Manik; Karmelita M Putri; Talitha Rebecca Octavia Lim; Nicholhas Jurdy Wijaya; Zefanya Octaberi; Yumi; Jeni Kristisia; Jeni Utary; Octa Nuria Peronica; Oria Mahestriabella; Malla Sinha Dora Br Ginting (Adiba Aisha Amira, 2025)
Community Service Program (KKN) is a form of student dedication to society aimed at providing real contributions to solving social and environmental problems. The Regular KKN Program of Group 7 from the State Christian Institute of Palangka Raya (IAKN) was implemented in Garung Village, Jabiren Raya District, Pulang Pisau Regency, during July–August 2025. The main problems identified were poor environmental hygiene due to unmanaged household waste, lack of adequate disposal facilities, and low public awareness of clean living behavior. This community service employed the Participatory Action Research (PAR) method with a qualitative descriptive approach, using observation, interviews, Focus Group Discussions (FGD), village transects, and field documentation. The core programs included the construction and installation of communal trash bins, socialization and education on environmental hygiene, joint clean-up activities, and the establishment of a Volunteer Garbage Task Force (Satgas Relawan Sampah). The results indicated an increase in community awareness of hygiene, the availability of simple waste management facilities, and the formation of local institutional support through the task force as a sustainability effort. This community service confirms that a participatory qualitative approach is effective in fostering a clean-living culture and strengthening community participation in maintaining a healthy village environment.